2018
DOI: 10.11646/zootaxa.4459.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Description of two new species of Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Western Ghats of Kerala, India

Abstract: Two new species of geckos of the genus Cnemaspis Strauch, 1887 are described from the southern Western Ghats of Kerala. Both species are medium to large sized Cnemaspis and can be differentiated from all other Indian congeners by a suite of distinct morphological characters. Both species are found in the high elevation forests of the two major massifs—       Anaimalai Hills and Agasthyamalai Hills and are presently known to have very restricted distributional ranges. The discovery of these novel species highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 772 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Several recent studies have explored the phylogenetic relationships within SA Cnemaspis ( Agarwal et al, 2017 , Cyriac et al, 2018 , 2020 , Khandekar et al, 2019a , 2019b ) as well as the evolutionary origin of lineages within the group ( Agarwal et al, 2020b ). However, these previous studies did not adequately sample the WG, where the genus is most diverse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have explored the phylogenetic relationships within SA Cnemaspis ( Agarwal et al, 2017 , Cyriac et al, 2018 , 2020 , Khandekar et al, 2019a , 2019b ) as well as the evolutionary origin of lineages within the group ( Agarwal et al, 2020b ). However, these previous studies did not adequately sample the WG, where the genus is most diverse.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 240 Cnemaspis individuals were examined for morphological analyses, including type specimens of the new lineages described herein as well as extant species from Peninsular India, topotypical specimens, type specimens, and other museum specimens listed in the material examined section (Appendix II). Comparative data on the described Cnemaspis species from Peninsular India were also taken from published literature ( Agarwal et al, 2020b ; Cyriac & Umesh, 2013 , 2014 ; Cyriac et al, 2018 , 2019 , 2020 ; Das & Bauer, 2000 ; Giri et al, 2009a , 2009b ; Khandekar, 2019 ; Khandekar et al, 2019a , 2019b , 2020b ; Manamendra-Arachchi et al, 2007 ; Mirza et al, 2014 ; Mukherjee et al, 2005 ; Murthy et al, 2019 ; Sayyed et al, 2016 , 2018 , 2019 , 2020 ; Srinivasulu et al, 2015 ). Counts and external observations of morphology and meristic characters were made under a Leica stereo dissecting microscope, and on the left side of the body for symmetrical characters where possible.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, 47% of the reptiles that occur here are endemic to the Western Ghats (Srinivasulu et al., 2014). Recent studies have also indicated that each mountain range in the Western Ghats possibly has many local endemics and basal lineages—especially in case of reptiles (Chaitanya et al., 2019; Cyriac et al., 2018; Deepak et al., 2020; Mallik et al., 2019; Pal et al., 2018). Consequently, there is a need to better document and explain patterns of species richness in this region.…”
Section: Introductionmentioning
confidence: 99%